Teachers’ Emotional Management Strategies in EFL Students’ Speaking Learning Process - Fadhillah, Raehanun; Basri, Muhammad; Halim, Abd. (Journal of Excellence in English Language Education, 2024)
This research aims to explore teachers’ perceptions, teachers’ strategies and the impact of emotional management on students’ speaking learning processes in EFL (English as a Foreign Language) classrooms. This research is qualitative research with a thematic analysis. The subject of this research is English Teacher who actively teaches in Athirah Islamic Senior High School. Data were collected through questionnaires distributed to teachers and semi-structured interviews with five English teachers at Athirah Islamic High School. The findings indicate that teachers have a positive perception of the importance of emotional management in facilitating effective speaking instruction and creating a conducive learning environment. Key strategies teachers implement encompass constructive learning approaches, establishing psychological safety, and building positive teacher-student relationships. Specific examples include using engaging activities, self-reflection, role modeling calmness, giving encouragement, and developing interpersonal bonds. In terms of impacts, managed teacher emotions translated into increased students’ enthusiasm, class participation, achieved competencies, and reduced speaking anxiety. Students mirrored teachers’ stability and emotional balance, loosening inhibitions around verbal participation. By contrast, poor emotional regulation transferred pressures onto students, disrupting engagement. Hence, teachers’ emotions significantly influence the classroom climate and student speaking outcomes. This study concludes that concerted emotional management and student-centered strategies enable teachers to unlock participation, foster resilience, and facilitate the repetitions essential for English speaking mastery. Findings will equip educators to create affectively supportive environments conducive to oral language development.